The development of a method for identifying penalty kick strategies in association football - Noël, B.; Furley, P.; van der Kamp, J.; Dicks, M.; Memmert, D. (Journal of Sports Sciences, 2015)
Penalty takers in association football adopt either a keeper-independent or a keeper-dependent strategy, with the benefits of the keeper-independent strategy presumed to be greater. Yet, despite its relevance for research and practitioners, thus far no method for identifying penalty kick strategies has been available. To develop a validated and reliable method, Experiment 1 assessed characteristics that observers should use to distinguish the two strategies. We asked participants to rate 12 characteristics of pre-recorded clips of kicks of penalty takers that used either a keeper-independent or keeper-dependent strategy. A logistic regression model identified three variables (attention to the goalkeeper, run-up fluency and kicking technique) that in combination predicted kick strategy in 92% of the penalties. We used the model in Experiment 2 to analyse prevalence and efficacy of both the strategies for penalty kicks in penalty shoot-outs during FIFA World Cups (1986-2010) and UEFA Football Championships (1984-2012). The keeper-independent strategy was used much more frequently (i.e., 78-86%) than the keeper-dependent strategy, but successes did not differ. Penalty takers should use both the strategies to be less predictable. Goalkeepers can use the developed model to improve their chances to succeed by adjusting their behaviour to penalty takers` preferred penalty kick strategy.